Kontribusi Pendidikan Agama Kristen terhadap Kesehatan Mental Remaja Kristen Indonesia di Era Digital - Sri Radandima; Resa Junias (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2026)
Indonesian adolescents spend an average of 8.8 hours per day online (APJII, 2024), driving rising anxiety, depression, cyberbullying, and identity crises. Research on adolescent digital mental health has concentrated on psychological interventions and platform regulation, while overlooking the strategic role of Christian Religious Education (CRE) as a system for holistic mental health formation. This study analyses CRE's contribution to adolescent mental health in the digital era through three mechanisms: identity formation grounded in theological values, spiritual resilience building, and self-control development. The method combines a descriptive qualitative design with library research and semi-structured interviews with 12 informants (4 CRE teachers, 5 adolescents, 3 parents). Findings show that CRE implemented integratively through family-school-church collaboration builds measurable and consistent psychological resilience in adolescents.